1967
DOI: 10.1017/s0022172400045812
|View full text |Cite
|
Sign up to set email alerts
|

Edwardsiella tardain a study of juvenile diarrhoea

Abstract: Four strains ofEdwardsiella tarda, a recently described member of the Entero-bacteriaceae, were studied, They were isolated from four out of 832 children during a 3-year survey of juvenile diarrhoea at Vellore, S. India. Three of the four children had diarrhoea when the organisms were isolated and one was convalescent from bacillary dysentery. From this study and a review of the literature it appears thatEd. tardais found only infrequently in man and that its main reservoir may be in animals such as snakes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 7 publications
(2 reference statements)
0
17
0
Order By: Relevance
“…Limited data are available on the susceptibility to antibiotics of the recently described Edwardsielkl tarda. Both strains studied by von Graevenitz and Nourbakhsh (18), as well as four strains studied by Bhat et al (2) and three strains studied by Jordan and Hadley (11), appeared to be resistant to colistin. If it could be shown that resistance to colistin is a general property of Edwardsiella, and if the margin between inhibitory concentrations for Edwardsiella and for reputedly sensitive Enterobacteriaceae were large enough, then colistin resistance could be used as a differential marker in identification.…”
mentioning
confidence: 78%
“…Limited data are available on the susceptibility to antibiotics of the recently described Edwardsielkl tarda. Both strains studied by von Graevenitz and Nourbakhsh (18), as well as four strains studied by Bhat et al (2) and three strains studied by Jordan and Hadley (11), appeared to be resistant to colistin. If it could be shown that resistance to colistin is a general property of Edwardsiella, and if the margin between inhibitory concentrations for Edwardsiella and for reputedly sensitive Enterobacteriaceae were large enough, then colistin resistance could be used as a differential marker in identification.…”
mentioning
confidence: 78%
“…Human isolations reported in America by Ewing et al (1965), Jordan & Hadley (1969) and from India by Bhat et al (1967) indicate that the organism may be present both with and without symptoms in juveniles and adults. The species has also been recovered in America from a fatal adult meningitis case by Sonnenwirth & Kallus (1968) and from a neonatal meningitis, also fatal, reported from Nigeria by Okubadejo & Alausa (1968).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the four Salmonella subgenera, few details of culture procedures have been published. However, in India, Bhat, Myers & Carpenter (1967) reported four Edwardsiella isolations from children and commented that colonies on MacConkey and deoxycholate agar resembled Salmonella species. The organisms grew on bismuth sulphite agar and survived culture in selenite F broth.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] She collaborated with international laboratories for a landmark study on juvenile diarrhoea caused by Edwardsiella tarda. [24] During the span of her illustrious career, she was also instrumental in serogrouping of EPEC -5 -14 and establishing in vitro culture of P. falciparum in her laboratory.…”
Section: Women In Medical Microbiologymentioning
confidence: 99%